2015
DOI: 10.31768/2312-8852.2015.37(4):285-291
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Ultrasonography in Pancreatic Surgery: Staging and Resection Guidance

Abstract: Background: Intraoperative ultrasound examination (IOUS) is indispensable part of modern surgical interventions in tumors of hepatopancreatobiliary zone. In this study retrospective analysis of IOUS efficiency in surgical treatment of pancreatic tumors was provided. Materials and Methods: In the period from January 2013 till November 2015 in the National Cancer Institute IOUS was applied during 76 surgical interventions: for pancreatic head tumors — in 46 (60.5%) patients, for body/tail pancreatic tumors — in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Also intraoperative Doppler ultrasound was used to identify the boundaries of pancreatic mass and to determine the transection line of the pancreas, as well as to identify the splenic vessels. 46,47 We herein present the first case of totally robotic distal pancreatectomy, left hemihepatectomy and splenectomy for PNET with no severe perioperative comorbidity and optimal oncologic outcomes. As the tumor was stable and localized in just pancreas and liver, she was offered surgery with both curative and cytoreductive intent.…”
Section: Discussionmentioning
confidence: 97%
“…Also intraoperative Doppler ultrasound was used to identify the boundaries of pancreatic mass and to determine the transection line of the pancreas, as well as to identify the splenic vessels. 46,47 We herein present the first case of totally robotic distal pancreatectomy, left hemihepatectomy and splenectomy for PNET with no severe perioperative comorbidity and optimal oncologic outcomes. As the tumor was stable and localized in just pancreas and liver, she was offered surgery with both curative and cytoreductive intent.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies on IOUS in pancreatic cancer have mainly focused on the detection of metastases, rather than the evaluation of vascular involvement. [21][22][23][24] A previous prospective monocenter study by our group suggested that IOUS could be useful, as it downstaged the local resectability status in one-third of 38 patients with LAPC after induction chemotherapy. 14 Another monocenter study by our group included 31 patients with pancreatic ductal adenocarcinoma (PDAC), or periampullary cancer, and indicated more accurate assessment of vascular involvement by IOUS, compared with conventional imaging modalities.…”
Section: Discussionmentioning
confidence: 99%
“…Visual inspection, palpation, and IOUS are intraoperative modalities to identify pancreatic lesions and their borders. However, small pancreatic lesions are not clearly identified or are unidentified even using all modalities (13% of our series).…”
Section: Discussionmentioning
confidence: 99%